KONTRIBUSI HASIL BELAJAR MATA DIKLATKEWIRAUSAHAANTERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI SMKNEGERI 2 SAWAHLUNTO - 2041-2047, Bayu Mahendra (CIVED, 2018)
Abstract—This research is motivated from the high percentage of unemployed vocational high school graduates and low interest of students to entrepreneurship in accordance with the field of expertise it has. This study aims to reveal the Contribution of Learning Outcomes of Entrepreneurship Training Course to Students Entrepreneurship Interest in Class XI SMK Negeri 2 Sawahlunto.The type of this research is correlation research with population of all students of class XI Department of Building Image Engineering as many as 183 people. The sample of 126 students is taken using proportional random sampling technique. The type of data used is primary and secondary data. Primary data obtained through questionnaires distributed to students, while secondary data is the result of learning in the form of semester grades of students of class XI SMK Negeri 2 Sawahlunto. Data analysis techniques used are: 1) Descriptive analysis, 2) Test requirements analysis, consisting of normality test and linearity test to prove that the distribution of data derived from samples of normal and linear distributed, and 3) Hypothesis Testing.From the results of research that has been done, it can be concluded with the Contribution of Learning Outcomes of Entrepreneurship Training Course on Students Entrepreneurship Interest in Class XI SMK Negeri 2 Sawahlunto of 28.62%, the remaining 71.38% is owned by other factors not examine.Keywords:Interest, Entrepreneurship, Learning Outcomes